Transvesical Intra-Abdominal Pressure Measurement in Newborn: What Is the Optimal Saline Volume Instillation?*. Issue 2 (February 2016) - Defontaine, Anne; Tirel, Olivier; Costet, Nathalie; Beuchée, Alain; Ozanne, Bruno; Gaillot, Théophile; Arnaud, Alexis Pierre; Wodey, Eric
Abstract : Objective: To determine the optimal saline volume bladder instillation to measure intravesical pressure in critically ill newborns weighing less than 4.5 kg, and to establish a reference of intra-abdominal pressure value in this population. Design: Prospective monocentric study. Setting: Neonatal ICU and PICU. Patients: Newborns, premature or not, weighing less than 4.5 kg who required a urethral catheter. Measurements and Main Results: Patients were classified into two groups according to whether they presented a risk factor for intra-abdominal hypertension. Nine intravesical pressure measures per patient were performed after different volume saline instillation. The first one was done without saline instillation and then by increments of 0.5 mL/kg to a maximum of 4 mL/kg. Linear models for repeated measurements of intravesical pressure with unstructured covariance were used to analyze the variation of intravesical pressure measures according to the conditions of measurement (volume instilled). Pairwise comparisons of intravesical pressure adjusted mean values between instillation volumes were done using Tukey tests, corrected for multiple testing to determine an optimal instillation volume. Forty-seven patients with completed measures (nine instillations volumes) were included in the analysis. Mean intravesical pressure values were not significantly different when measured after instillation of 0.5, 1, or 1.5 mL/kg, whereas measures after instillation of 2 mL/kg or more were significantly higher. The median intravesical pressure value in the group without intra-abdominal hypertension risk factor after instillation of 1 mL/kg was 5 mm Hg (2–6 mm Hg). Conclusions: The optimal saline volume bladder instillation to measure intra-abdominal pressure in newborns weighing less than 4.5 kg was 1 mL/kg. Reference intra-abdominal pressure in this population was found to be 5 mm Hg (2–6 mm Hg).